Towards Circular Consent in African Studies - Abdul-Gafar Oshodi (Nordic Journal of African Studies, 2025)
Consent forms are crucial in the approval of research projects by ethics committees within and outside Africa. However, the current formalization and standardization of consent inadvertently limits the ability of researchers and participants to expand the idea of agreement and navigate assent within and beyond the field. This intervention invites researchers to rethink the idea of consent – as an action, an approach, and a process – by exploring circular consent, which centres research participants in the research process. While broadening the idea of consent, circular consent offers an approach that expands participants’ agency beyond one-off forms and pragmatically accommodates changing views in the research process. Beyond discussing its four ‘legs’ (i.e., reflexivity, feedbacking, incentivization, and flourishing), the paper identifies and discusses some dilemmas that make circular consent a difficult task in the current North-South research ecosystem. By raising the issue of power, funding, and timing in the research process, this paper contributes to the debate about the functionality of consent forms as prioritized in contemporary research processes. A reflection on methodological and ethical choices in the research process, this paper stems from the author’s experience during two research projects in Ghana.